Fatty acid composition of milk of refugee Karen and urban Korean mothers. Is the level of DHA in breast milk of Western women compromised by high intake of saturated fat and linoleic acid? - Golfetto, I; McGready, R; Ghebremeskel, K; Min, Y; Dubowitz, L; Nosten, F; Drury, P; Simpson, JA; Arunjerdja, R; Crawford, MA (SAGE Publications, 2007)
Background: Lower proportions of docosahexaenoic acid (DHA) and total n-3 metabolites have been reported in breast milk of European, Australian and North American women compared with milk of mothers from non-Western countries. This difference is not always explained by intakes of marine products.